Cystatin C could be a replacement to serum creatinine for diagnosing and monitoring kidney function in children (2008)
Background: Chronic kidney disease (CKD) is a worldwide public health problem. Glomerular filtration rate (GFR) is accepted as the best way to diagnose and monitor kidney function. Plasma Cystatin C (CysC) has been proposed as a better marker of GFR than serum creatinine (SCr), but it is not widely used because of some drawbacks with CysC assays. Our purpose is to determine the diagnostic accuracy of CysC and SCr for GFR estimation in children, using 99Tc-DTPA clearance (ClTc) as the reference standard. We also discuss some of the economic implications of these tests, in order to guide clinicians when to use CysC or SCr for the diagnosis or monitoring of CKD. Methods: Data were collected from 109 Colombian outpatients aged less than 18 years referred for determination of GFR because of suspected or definite renal insufficiency. The cost of each test was determined in Bogotá, Colombia, and in Madrid, Spain. Results: Using a GFR of 90 mL/min as a cut-off value, we found: CysC sensitivity 75%, specificity 84%, and area under ROC curve (AUC) 0.84. SCr sensitivity 46%, specificity 100%, and AUC 0.72. Using a GFR of 70 mL/min as a cut-off value, we found: CysC sensitivity 100%, specificity 48%, and AUC 0.94. SCr sensitivity 77%, specificity 91%, and AUC 0.81. In all calculations predictive values behave correspondingly and ranges were narrow at CI 95%. In AUC, p = 0.0001. Cost per enzymatic test in Bogotá: CysC U$ 27; SCr U$ 2. Cost per enzymatic test in Madrid: CysC U$ 3; SCr U$ 0.08. Conclusion: CysC is a very interesting option, and could be a replacement to serum creatinine for diagnosing and possibly for monitoring kidney function in children.